Der skal ikke lades sten på sten tilbage - Andersen, Harald (Kuml, 1956)
The Building by the Barbar Temple Close by the large temple at Barbar 1) lies a little tell, which was investigated in the spring of 1956. The tell was shown to cover a building of stone and plaster construction. Only portions of the building were uncovered, though enough to reveal in main outline the problems of the site. On the open plain a floor had been laid of stone-reinforced plaster. On this floor two squares of walling had been erected, the one within the other. The outer wall did not extend quite to the edge of the plaster floor, but left a sidewalk uncovered. Between the two walls a narrow passage goes all the way round the building. The floor, which is somewhat damaged, was probably originally approximately square, with a width of about 24 metres. The damage has mainly affected the sidewalk which has been broken up in many places. Within the outer wall the floor is reasonably complete except for a large hole in the centre of the building. Towards the east and north the floor has subsided 30-40 cms. under the weight of the wall and is covered with deep cracks. Stone robbers have dealt hardly with the inner wall. Not a single stone remains, but the impress of the wall in the plaster of the floor remained in most places clearly to be seen. The outer wall had been broken down much less systematically. In many places not merely the wall but also the floor under it had been taken; in other places the floor remained, and with it the imprint of the wall; and in three places there even remained portions of the wall itself - though only of the inner surface. The best preserved wall-fragment retained a height of about one metre. The masonry was coarse, put together of poorly shaped blocks and unshaped stones, all set in plaster. The inner surface of the wall was coated with plaster, and everywhere in this plaster layer could be seen the grooves left by smoothing fingers. Lying outside the eastern limits of the building, a number of large, regularly shaped ashlar blocks were found, of the same light-coloured limestone as was employed so liberally in the large Barbar temple 2). These stones must have come originally from the outer wall, and belonged perhaps to a gateway; no other trace of door or gateway has been found, either in actual masonry or in imprint. A little geometrical drawing was found scratched on a stone in the outer wall; it must have been made after the wall was broken down. Wind and weather had clearly worn hard upon the sidewalk to the east and south of the building. Neither in the passage nor in the inner enclosure, however, could similar signs of wear be seen, nor, remarkably enough, on the sidewalk to the west of the building. In the space inside the walls the plaster of the floor lay fresh as though newly laid, apparently scarcely worn at all. In the plaster were many clear imprints of naked feet, a very few prints of hands and the impress of a woven mat. Clearly the floor was taken into use before the plaster was dry. At several points there were moreover impressions of ropes, which presumably had been stretched from wall to wall. The ropes probably served as measuring and datum lines during the erection of the building. In the passage between the two walls two thin plaster layers were found at varying heights above the floor. Both layers - especially, as might be expected, the upper one - had been badly damaged when the walls were broken up, but there can scarcely be any doubt that they originally both stretched from wall to wall and all the way round the building. These plaster layers can hardly be other than floors laid to be walked on. The original floor must therefore have become covered with earth, and above this layer of earth a new floor has been laid. This process has later been repeated. In the centre of the building there was no plaster layer, but two hard layers in the earth covering the floor corresponded approximately in level with the plaster layers and may be assumed to represent the floor levels. These layers of earth supply the explanation of the noticably slight amount of wear on the original floor. The story of the destruction of the building contains features of interest. The inner wall has been broken up by the following process: the wall has been dug free, and the stones thereafter removed without any appreciable damage to the floor; the quarry trench has been left open and has later filled with drift sand; in this sand-filled trench only a few chips and fragments of stone were found. The case is very different in the layers which must be associated with the destruction of the outer wall. Here great heaps of fragments were found; in places the heaps stretched out over the sidewalk and far outside the area of the building. Everything points to the conclusion that the outer face of the building, its sidewalk and its surroundings were not covered with earth at all at the time when the outer wall was broken down. It seems therefore that the interior of the building was filled with considerable amounts of earth, while its outer face lay free and uncovered. Why can this be? Can the filling of the interior of the building be connected with the considerable subsidence of the building's northeast corner? Was it an attempt to level the sloping floor? The contrast between the lack of stone in the inner quarry trench and the great heaps of debris from the outer wall may probably be best explained thus: the inner wall was removed because there was need for stone elsewhere; the outer wall, on the contrary, was broken down to destroy, to render the building uninhabitable. The destruction hole in the middle of the building could be traced from the top of the mound to a point 1 ¼ metres below the bottom of the plaster floor. The greater part of the hole was full of stone and building debris, among which were found large ashlar blocks of light-coloured limestone, carefully shaped. Here too the digging must have been destructive in intent, not aimed at obtaining building material. The object of destruction was probably a roof-bearing pillar; at least, if a roof to the wide central area be assumed there must certainly have been a supporting pillar at this point. Scattered throughout the building were large quantities of potsherds - often of the ridged ware which is found in great amounts in the large Barbar temple, and which is known from the earliest Royal Graves at Ur, dated to about 3000 BC 3). The ridged sherds were found in large numbers under the lower of the two plaster levels in the passage - in other words, in a layer which can with certainty be attributed to the first period during which the building was in use. The building is therefore probably contemporary with the large temple building, most likely with its latest phase; for the little building contained shaped stone (including the limestone block here described) which most probably came from the temple. The destruction of the outer wall appears to have occurred at an early date in the building's life, while it was still in use. lf the building had been an abandoned ruin at the time of this destruction the sidewalk and the surrounding area would certainly have been covered by drift sand. The discovery of a heap of sherds above the debris level from the south wall also supports the view that the destruction took place as early as the "Barbar Period". The destruction in the centre of the building seems most probably to have occurred at the same time as the destruction of the outer wall. On the other hand, there is reason to believe that the breaking up of the inner wall - or at least its final removal - is of more recent, perhaps very recent, date. The sudden and thorough destruction of the building must certainly be seen as the result of enemy action. In the earliest written records of this region of the world we find innumerable accounts of the violence which the victors employed towards the property of the vanquished. Harald Andersen